Ethical education in teacher studies – pilot study analysis - Pękala, Joanna L. (Forum Pedagogiczne, 2020)
The following text presents the results of pilot studies on the condition of the ethical preparation of students of teaching faculties. A thesis was put forward that ethical competences are to a certain extent a set of specific skills that can and should be acquired and practiced during university preparation for the teaching profession. 50 students were included in the pilot study conducted using the diagnostic survey method in a form of a questionnaire. The hypothesis that students believe in importance of high ethical competence in the teacher’s professional work was confirmed. Respondents indicated the changes required by university education in the discussed area and the desired transformations listed the need for solving practical problems in ethics classes. The project’s author assumes current deficiencies in the preparation of future teachers for the performance of their professional work are related to the methods, and partly also to the content provided during ethics courses at universities.